Macam-macam tarif pajak dan dasar pengenaan pajak - Jauharoh, Sonia Zumna (Maliki Interdisciplinary Journal, 2025)
This article discusses various types of tax rates and tax bases in Indonesia’s taxation system. Tax rates consist of four main types: fixed (constant, such as 11% VAT and Rp10,000 stamp duty), proportional (same percentage, such as 0.5% land and building tax), progressive (increasing, such as Article 17 Income Tax for individuals), and regressive (decreasing for large objects, rarely used due to being less fair). Tax rates function as budgetary and regulatory tools for fiscal justice, equity, and economic stability, and are flexibly regulated through the Fiscal Policy and Taxation Harmonization Law.​ The tax base includes the Tax Base (for VAT/Income Tax such as net selling price), turnover (final Income Tax 0.5% for smes up to Rp4.8 billion/year), sales value (vehicle tax/vehicle transfer without VAT), import/export value (import duty/VAT with 0% export facilities), and replacement value (intangible services under Article 8A of the VAT Law). Understanding this is crucial for accurate calculations and compliance.